Panax Notoginseng Saponins Ameliorate Aβ-Mediated Neurotoxicity in C. elegans through Antioxidant Activities. (4th June 2019) - Zhou, Ling; Huang, Pan-Pan; Chen, Lin-Lin; Wang, Ping
Abstract : The deposition of amyloid beta (A β ) is the main hallmark of Alzheimer's disease (AD) and there is no effective drug to cure the progressive cognitive loss or memory deficits caused by the aggregative toxicity of A β protein. Oxidative stress has been hypothesized to play a role in progressive neurodegenerative diseases like AD. Panax notoginseng saponin (PNS) from the rhizome of " pseudo-ginseng " exhibits potent antioxidant effects on aging process in neuron cells and animals. By using C. elegans as an ideal model organism, the present study shows that PNS (0.5–4 mg/mL) can significantly inhibit AD-like symptoms of worm paralysis and enhance resistance to oxidative stress induced by paraquat and aging conditions. Additionally, PNS extends lifespan and maintains healthspan of C. elegans by improving the swimming prowess and fertility at old age. It markedly activates the expression of SKN-1 mRNA, which further supports SKN-1 signaling pathway which is involved in the therapeutic effect of PNS on AD C. elegans . Our results provide direct evidence on PNS for treating AD on gene level and theoretical foundation for reshaping medicinal products of PNS in the future.